Penerapan Deep Breathing Exercise dan Terapi Dzikir dalam Asuhan Keperawatan pada Pasien Fraktur Femur dengan Nyeri Akut di Ruang Trauma Center Irna Bedah RSUP Dr. M. Djamil Padang - Sarah Sabhira; Netti Netti; Suhaimi Suhaimi; Zulfa Zulfa (Jurnal Keperawatan Sehat Mandiri, 2025)
The main problem felt in a person who has a fracture is pain. Pain perception is personal and subjective; no two individuals perceive pain in identical patterns. Pain management can be done pharmacologically and non-pharmacologically. Non-pharmacological with deep breathing exercise and dhikr therapy can balance serotonin and norepineprin levels in the body and distract attention.. This study aimed to lower the scale of pain in fracture patients. Data from the Trauma Center room of Dr. M Djamil Padang Hospital for the last 3 months, namely February-April 20224, the number of femur fracture incidents is 62 cases. Descriptive observational research design in the form of a case report. The study was conducted in the Trauma Center Room of RSUP Dr. M Djamil Padang. The research time is from April 16-May 4, 2024. The population was all femoral fracture patients with a sample of 2 people taken by accidental sampling.The results of the application of deep breathing exercise and dhikr therapy showed a decrease in pain intensity before the intervention, namely a scale of 7 in the first patient and 6 in the second patient, after being given finger grip relaxation therapy, which was a scale of 3 in the first patient and 2 in the second patient.